The Effect of Fixed Asset Turnover, Capital Structure, Dividend Policy and Company Size on the Value of Property and Real Estate Companies Listed on the IDX - Siti Dini; Anjeli Saraswati; Berliana Fangly Putri (Publikasi Indonesia, 2022)
The purpose of this study was to examine the effect of fixed asset turnover, capital structure, dividend policy and firm size on firm value in property and real estate listed on the Indonesia Stock Exchange for the 2018-2020 period, either partially or simultaneously. Companies with sales that continue to grow will influence the investment decisions of investors who want to invest in companies that will get a high rate of return. The company will add more assets, so that increased company growth will optimize the value of the company. The population of this study are all property and real estate listed on the Indonesia Stock Exchange for the 2018-2020 period, which are 60 companies and a sample of 36 units of analysis. The data collection technique used in this research is purposive sampling. The results of the study show that the variables of fixed asset turnover, capital structure, dividend policy partially have a negative and significant effect on firm value in property and real estate the Indonesia Stock Exchange for the 2018-2020 period. The company size variable partially has a positive and significant effect on company value in property and real estate listed on the Indonesia Stock Exchange for the 2018-2020 period. Variables of fixed asset turnover, capital structure, dividend policy and firm size simultaneously significantly influence the firm value of property and real estate listed on the Indonesia Stock Exchange for the 2018-2020 period.